A STUDY OF THE IMPACT OF CLIMATE CHANGE ON RUBBER PRODUCTION IN OGAN KOMERING ULU REGENCY - Paulus Wisma Hadi; Yetty Oktarina; Yunita Sari; Fifian Permata Sari Fifian; Dadang Kurnia (Bajang Institute, 2022)
This study examines the impact of climate change, especially rainfall on rubber production in OKU Regency. The research method used in this study is the library method using rainfall data for 2010-2020 and rubber production data for OKU Regency. This research was conducted intentionally in OKU Regency considering that the majority of OKU people cultivate rubber as their main livelihood. The study was conducted in March 2022. The research data were analyzed using multiple regression analysis to analyze the impact of climate to rubber production in OKU Regency. Based on the results of the study with the regression analysis shows that each climate element has a significant effect on rubber production. By looking at this conclusion, the authors made observations in the field to prove the test results in the regression analysis carried out. Based on observations in the field, an increase in rainy days with low intensity can cause the loss of tapping days which is influenced by wet tapping paths so that tapping is not possible.